2006
DOI: 10.1029/2005gl025082
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atmospheric submonthly oscillations on sea surface temperature of the tropical Indian Ocean

Abstract: [1] Impacts of atmospheric intraseasonal oscillations (ISOs) at submonthly periods (10 -30 days) on Indian Ocean sea surface temperature (SST) are studied using satellite observed outgoing long wave radiation, QuikSCAT winds, SST and an ocean general circulation model for the period of 1999 -2004. The results suggest that submonthly ISOs can cause significant 10 -30 day SST changes throughout the equatorial basin and northern Bay of Bengal, with an amplitude of as large as 0.5°C and standard deviation of excee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…The peaks of the cooling episodes typically lag the . This is in agreement with a recent study of Han et al [2006] who have shown that the atmospheric intraseasonal oscillations can cause significant changes in SST on time scale of 10-30 days in the equatorial Indian Ocean.…”
Section: Mechanisms Of Cooling Episodes On Intraseasonal Time Scalesupporting
confidence: 94%
“…The peaks of the cooling episodes typically lag the . This is in agreement with a recent study of Han et al [2006] who have shown that the atmospheric intraseasonal oscillations can cause significant changes in SST on time scale of 10-30 days in the equatorial Indian Ocean.…”
Section: Mechanisms Of Cooling Episodes On Intraseasonal Time Scalesupporting
confidence: 94%
“…12b, the effects of winds dominate the SST variability, whereas the heat flux induced by the MJO can affect the amplitude of SST variability slightly. The dominant role of winds on SST is similar to the case in the Indian Ocean (Han et al 2007). …”
Section: B Ocean Circulation Response To Mjomentioning
confidence: 52%
“…It is characterized by atmospheric circulation and moist convection anomalies that propagate eastward from the Indian Ocean to the western Pacific. The MJO can influence rainfall in many regions, modulating the weather systems and interacting with the ocean (Jones et al 1998;Maloney and Hartmann 2000;Morita et al 2006;Han et al 2006Han et al , 2007Huang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More specific ISOs are identified to have a large influence on the Asian summer monsoon (e.g. Sikka and Gadgil 1980, Yasunari 1981, Krishnamurti and Subramanyam 1982, Webster 1983, Wang and Xie 1997, Lawrence and Webster 2002, Webster and Hoyos 2004, the Indian Ocean dipole (Han et al 2006, Chowdary and Gnanaseelan 2007, Thompson et al 2009) and ENSO (McPhaden 1999, Moore and Kleeman 1999, Takayabu et al 1999, Kessler and Kleeman 2000, Kiladis and Straub 2001.…”
Section: Intraseasonal Variability In Avhrr and Amsr-avhrr Sstmentioning
confidence: 99%
“…The microwave data depends also on emissivity and therefore on surface roughness and sea state. The importance of daily SST over the tropical Indian Ocean is now being increasingly recognized , Chongyin et al 2005, Han et al 2006. In this article, the emphasis is on analysis of the daily SST product, which has been made available recently at the National Oceanic and Atmospheric Administration (NOAA) as described by Reynolds et al (2007) over the tropical Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%